Pigmented villonodular synovitis of the knee in a child: Case report - Marić Dušan M.; Vučković Nada; Gajdobranski Đorđe R.; Drašković Biljana G.; Bekić Vesna; Jovanović Mladen; Petković Lazar D.; Marić Dušica L. (Archive of Oncology, 2004)
Pigmented villonodular synovitis (PVS) is a destructive fibrohistiocytic proliferation with production of villus and nodular protrusions in synovial membrane. A boy, aged 12 years, had a knee injury during a football game with severe pane, swelling, decreased range of motion, and presence of hemarthrosis. Magnetic resonance imaging revealed, in the projection of the suprapattelar recessus, tumefaction of irregular shape; the largest diameter 11x5 cm. Upper pole of tumefaction was partly impressed in m. vastus intermedius. In general endotracheal anesthesia partial synovectomy was done with complete extirpation of tumefaction. The diagnosis of pigmented villonodular synovitis was established histologically. This type of tumefaction is rare in children, but the adequate treatment is necessary because of its aggressive growth with possible bone destruction and propensity of recidivism. The suspicion of malignant neoplasm is often present. Due to various clinical presentation of villonodular synovitis, early detection and adequate treatment is necessary.